Preoperative transarterial embolization of vertebral metastases - Guzman, Raphael (Springer-Verlag, 2004)
The aim of this study was to evaluate the impact of preoperative devascularization of spinal metastases in relation to the preembolization tumor vascularization degree and in relation to the intraoperative blood loss. Twenty-four patients underwent preoperative transarterial embolization of hypervascular spinal metastases. Each tumor was assigned a vascularization grade (I–III) according to tumor blush after contrast agent injection in the main feeding artery. Embolization was performed with polyvinyl alcohol particles in all patients. Surgical reports were reviewed in terms of estimated blood loss. A mild hypervascularization was found in three patients (group I), medium in six patients (group II) and extensive in 15 patients (group III). In 22 out of 24 patients embolization could be performed with a complete devascularization. In two patients, only partial embolization could be performed, due to the main feeding artery arising from the artery of Adamkiewicz. In patients with complete devascularization the mean intraoperative blood loss was 1,900 ml, whereas in the two patients who were not embolized it was 5,500 ml. Intraoperative blood loss was not correlated to the vascularization grade. Angiography and embolization could be performed in all patients without causing permanent neurologic deficit, skin or muscle necrosis. The surgeons concluded that radical tumor resection after embolization was facilitated. Intraoperative blood loss is not correlated with the pre-interventional vascularization degree, if complete devascularization can be achieved with embolization. Preoperative embolization of vertebral hypervascular tumors is safe, effective and facilitates tumor resection.